Essays in political economy - Fabian Ruthardt (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2023)
This thesis examines the reciprocity between the economy and elections, politicians, and policies. To inform voters about the consequences of their ballot choices, understanding the triangular relationship between the economy, political actors, and policies is essential. In representative democracies, people do not elect policies. They elect politicians, who serve as imperfect intermediaries to carry out the people's will. The four chapters aim to improve transparency about the origins and effects of economic policies. They each address certain aspects of policy preferences, formulation, timing, and impact. While each chapter constitutes a self-contained study, I encourage the reader to follow the given structure: Chapter 1 studies the consequences of a specific tax reform, a tariff increase, for GDP growth, the balance of trade, and state finances. Chapter 2 investigates how politicians time tax policies around elections. Chapter 3 examines the influence of extraordinary politicians on global economic expectations. Chapter 4 connects local exogenous shocks to voters' policy preferences and electoral outcomes. Unanticipated events and electoral uncertainty are common themes of all papers. – – In dieser Dissertation wird die Wechselwirkung zwischen der Wirtschaft und den Wahlen, Politikern und Politik untersucht. Um die Wähler über die Folgen ihrer Wahlentscheidung zu informieren, ist das Verständnis der Dreiecksbeziehung zwischen der Wirtschaft, den politischen Akteuren und den Politiken von entscheidender Bedeutung. In repräsentativen Demokratien bestimmen die Bürger*innen nicht direkt die Politik. Sie wählen Politiker, die als unvollkommene Repräsentanten des Wählerwillens agieren. Die vier Kapitel zielen darauf ab, die Ursprünge und Auswirkungen der Wirtschaftspolitik transparenter zu gestalten. Sie behandeln jeweils bestimmte Aspekte von Politiken, insbesondere Präferenzen, Formulierungen, zeitliche Implementierungen und Auswirkungen. Während jedes Kapitel eine in sich abgeschlossene Studie darstellt, empfiehlt es sich, der vorgegebenen Struktur zu folgen: Kapitel 1 untersucht die Folgen einer speziellen Steuerreform, nämlich einer Zollerhöhung, für das BIP-Wachstum, die Handelsbilanz und die Staatsfinanzen. In Kapitel 2 wird dargestellt, wie Politiker ihre Steuerpolitik.
Keywords: A11; D72; F10; H20; O11; Q54; 330; Economic growth; elections; electoral cycles; government revenue; international trade; natural disasters; tax reforms; voter behavior